Commodity Price Shocks and the Oddson Fiscal Performance - Kumah, Francis; Matovu, John. (Washington, D.C. : International Monetary Fund, 2005)
Unanticipated changes in commodity prices can generate significant movements in fiscal aggregates. This paper seeks to understand the dynamics of these fiscal movements in the context of transitory commodity price shocks using sample data from four CIS countries- two oil-producing and two non-oil commodity-intensive countries. It adopts a structural VAR approach and identifies the dynamic effects of commodity price shocks on fiscal performance under two broad tax regimes. Stochastic simulations indicate high probabilities of fiscal overperformance in the short term when commodity prices are high. These probabilities deteriorate significantly, however, in the long term after the transitory positive commodity price shock has dissipated, particularly when lax fiscal policy is adopted during the period of the price boom.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet